Medical Toursm Sebagai Stategi Pemasaran Rumah Sakit: Narrative Review - Rusli, Peter (UI Scholars Hub, 2019)
To understand about the Medical Tourism as a part of Hospital Marketing Strategies in Tourism Area. Articles that included and assessed for the eligibility in this review was an article shown a Medical Tourism related to hospital marketing strategies in Indonesia. Medical Tourism is defined as the effort of the facility or tourist destination to attract tourists by promoting its health services and facilities, in addition to its regular tourist facilities, so that it emphasizes service providers. Hospitals as private businesses use various strategies to attract more patients / customers, such as creating therapeutic spaces in hybrid hotels (hospitals designed for the convenience of international patients). The hospital also develops a marketing strategy to direct patients and customers and identifies these three strategies - linking to potential patients through visits to home countries, employing medical travel intermediaries and developing 'medical check-up' packages for healthy people. Journal of Medical Tourism, Indonesia is still a part of contributors to medical tourists in Malaysia, amounting to 47.8 percent. Indonesia is still facing various health problems that remain unresolved so that it is still focused on the domestic marketing segmentation so that it has not reached or returned market segments from consumers or patients who utilize health services abroad. The study of the Medical Tourism system model is still growing and has a lot of potential using this model.The implementation Medical Tourism as hospital marketing strategis should be improved with future in Indonesia as a Tourism country.